CERITA RAKYAT SETING PE-GAMA ANING DUKA KATWALA DI DESA MAUKURU KECAMATAN ALOR TIMUR KABUPATEN ALOR - Orlando De Rois Lapuilana; Petrus Mau Tellu Dony (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research aims to describe and study Folklore Seting Pe-Gama Aning Duka Katwala in Maukuru Village, East Alor District, Alor Regency. This research uses descriptive qualitative method with the research subjects are the elderly people in Maukuru Village. Data collection techniques through observation for eight meetings. Based on the purpose of this study to measure the level of knowledge about customs and culture, especially folklore in Maukuru Village. First, how is the level of knowledge in terms of customs, second so that we as Maukuru Village community members (generations) can know the existing folklore, and third how do we preserve existing culture and folklore. Data presentation is done by using words to take facts, variables and circumstances obtained during the research and explain the words obtained.